Infection and autoimmunity: a two-way relationship - Cervera, Ricard (Henry Stewart Talks, 2007)
Viruses and autoimmunity, The role of HCV and HIV, Antiphospholipid syndrome and infections, Molecular mimicry, Infectious agents and antibodies to beta-2-glycoprotein I peptides
Reviewed at 2017/05/17